A Preliminary Framework of Forensic Science Fundamentals Based on its Elements in Shariah Manuscripts - Ahmad Syukran Baharuddin; Wan Abdul Fattah Wan Ismail; Fuadah Johari; Muhammad Aunurrochim Mas'ad Saleh (Penerbit USIM, 2024)
Forensic science has become an ‘odd’ to the shariah due to the dual educational system that segregationally treats science different from religion. As to stitch back the loophole, this study aims to identify forensic elements in classical legal scripts that can lead to the formation of integration theory. This study used Grounded Theory Method that relied upon constant comparative approach guided by literature analysis. The theoretical samples were gathered from classical legal opinions in the admissibility of circumstantial evidence in Islam. This study found that there were 117 free nodes that constantly built four key fundamentals for the framework which were forensics jurisprudence, human capital, forensic analysis, and accreditation. This study proved that there is a connection between science and religion through the application of forensics in Islamic legal scripts. This study suggests further exploratory research on each key fundamental found thus completes the theory development process of this framework.